The long-term rise of labor market detachment: Evidence from local labor markets - Jaison R. Abel; Richard Deitz (Federal Reserve Bank of New York, 2024)
We develop a measure of chronic joblessness among prime-age men and women in the United States - termed the detachment rate - that identifies those who have been out of the labor force for more than a year. We show that the detachment rate more than doubled for men since the early 1980s and rose by a quarter for women since 2000, though it is consistently considerably higher for women than men. We then explore the economic geography of labor market detachment to help explain its rise. Results show that the detachment rate increased more in places with weak local economies, particularly those that experienced a loss of routine production and administrative support jobs due to globalization and technological change. The loss of production jobs affected both men and women and was particularly consequential in the 1990s and the first decade of the 2000s, while the loss of administrative support jobs mostly affected women and was particularly severe in the 1980s and 1990s. Moreover, we find the rise in detachment was concentrated among older prime-age individuals and those without a college degree, and occurred less in places with high human capital.
Keywords: E24; J21; J24; J61; O33; R12; R23; 330; joblessness; labor force participation; local labor markets; job polarization; globalization; technological change; regional divergence